Optical Interferometry (IntechOpen, 2023)
Optical methods of measurements are the most sensitive techniques of noncontact investigations, and at the same time, they are fast as well as accurate which increases reproducibility of observed results. In recent years, the importance of optical interferometry methods for research has dramatically increased, and applications range from precise surface testing to finding extrasolar planets. This book covers various aspects of optical interferometry including descriptions of novel apparatuses and methods, application interferometry for studying biological objects, surface qualities, materials characterization, and optical testing. The book includes a series of chapters in which experts share recent progress in interferometry through original research and literature reviews.